2022
DOI: 10.1186/s43593-022-00031-1
|View full text |Cite|
|
Sign up to set email alerts
|

Upconversion nanoparticles for super-resolution quantification of single small extracellular vesicles

Abstract: Although small EVs (sEVs) have been used widely as biomarkers in disease diagnosis, their heterogeneity at single EV level has rarely been revealed. This is because high-resolution characterization of sEV presents a major challenge, as their sizes are below the optical diffraction limit. Here, we report that upconversion nanoparticles (UCNPs) can be used for super-resolution profiling the molecular heterogeneity of sEVs. We show that Er3+-doped UCNPs has better brightness and Tm3+-doped UCNPs resulting in bett… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 41 publications
0
21
0
Order By: Relevance
“…A remarkable recent study by Huang et al extended UCNPs to detect single EVs [ 129 ]. The authors found that while the Er 3+ -doped UCNPs had a better brightness, the Tm 3+ -doped UCNPs had a better resolution beyond the diffraction limit.…”
Section: Fluorescence Nanomaterialsmentioning
confidence: 99%
“…A remarkable recent study by Huang et al extended UCNPs to detect single EVs [ 129 ]. The authors found that while the Er 3+ -doped UCNPs had a better brightness, the Tm 3+ -doped UCNPs had a better resolution beyond the diffraction limit.…”
Section: Fluorescence Nanomaterialsmentioning
confidence: 99%
“…25 The 4f electron orbital endows most RE ions with abundant intermediate energy levels for electronic transitions, 26 enabling Ho 3+ , Nd 3+ , Er 3+ , and Tm 3+ to exhibit upconverted luminescence in the range from the UV band to near-infrared light (NIR). 27 The corresponding RE-based upconversion nanoparticles are well known for application in bioimaging, [28][29][30] photothermal therapy (PTT), [31][32][33] photodynamic therapy (PDT), 34,35 drug delivery, 36,37 and other biomedical fields. Interestingly, the unpaired electrons in the 4f layer and spin-orbital coupling also endow Ln 3+ paramagnetic candidates 38 with high magnetic moment and magnetic susceptibility as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, broad, deep-red lighting devices suitable for plant growth have become the focus [ 10 ]. At present, phosphor-converted light-emitting diodes (pcLEDs) based on blue chips, are among the most effective lighting means [ 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%